The role of academician Korzh A. A. in the development of pediatric orthopedics in Yevpatoriya central children’s clinical sanatorium of the ministry of defense of Ukraine - Nenko, Anatoliy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2016)
The paper analyzed an orthopedic and scientific assistance that was provided by Academician Korzh A. A. and scientists of the Kharkov Research Institute of Orthopedics and Traumatology named after prof. M. I. Sytenko to the specialists of Yevpatoriya Central Children’s Clinical Resort of the Ministry of Defense of Ukraine. Close cooperation between the two hospitals was aimed to the implementation of scientific research results and the achievements of the Institute specialists into the therapeutic and diagnostic work of sanatorium. This fact allowed doctors to master the technique of spinal and large joints surgery, bone grafting and surgical repair after poliomymyelitis and skeletal injuries, etc. All mentioned above improved the quality of medical and rehabilitative care for children with diseases of the musculoskeletal system. In addition, scientists of the Institute provided scientific-technical and advisory assistance in the organization of research, they also led the dissertation research managing by Yevpatoria colleagues. At the initiative of Korzh A. A. and with his direct participation the on-site thematic trainings in pediatric orthopedics were organized for doctors at the sanatorium using specialists from department of traumatology and orthopedics of the Ukrainian Institute of Advanced Medical. 18 scientific conferences were conducted at the sanatorium. The doctors of sanatorium prepared 442 reports in scientific medical journals; published 576 papers and defended 6PhD theses. International recognition of sanatorium as an effective orthopedic-surgical treating and rehabilitation institutions for children with diseases of the musculoskeletal system was one of the achievements of a fruitful collaboration.